The effects of chronic candesartan treatment on cardiac and hepatic adenosine monophosphate-activated protein kinase in rats submitted to surgical stress. (September 2015) - Ribeiro-Oliveira, Antônio; Marques, Mirna B; Vilas-Boas, Walkiria W; Guimarães, Jonas; Coimbra, Cândido C; Anjos, Allan P; Fóscolo, Rodrigo B; Santos, Robson; Thomas, Julia D; Igreja, Suzana M; Kola, Blerina; Grossman, Ashley B; et al.
Introduction: adenosine monophosphate-activated protein kinase (AMPK) plays a prominent role as a metabolic stress sensor, and it has recently been suggested that the renin-angiotensin system, in addition to its role in stress regulation, may play a significant role in regulating the AMPK system. This study aimed to evaluate the effects of candesartan, an angiotensin II receptor blocker, on cardiac and hepatic AMPK activity basally as well as after surgical stress under general anesthesia. Materials and methods: Male Wistar rats were treated with 5 mg/kg/day candesartan in their drinking water for two weeks. Levels of cardiac and hepatic AMPK activity were determined, using a kinase activity assay, basally and after surgical stress under general anesthesia. Results: Chronic administration of candesartan increased hepatic AMPK activity approximately 4 times ( p <0.05) while no significant change was demonstrated in cardiac AMPK. Cardiac and hepatic AMPK activities were not significantly increased by surgical stress alone performed under anesthesia. However, chronic treatment with candesartan decreased AMPK activity in both liver and heart after surgical stress under anesthesia ( p <0.01 for both comparisons). Conclusions: While chronic candesartan treatment may stimulate AMPK activity in certain organs such as the liver, when combined with surgical stress under anesthesia it inhibits pathways regulating AMPK activity.